The Effect of Islamic Financial Inclusion, Urbanization, Inflation, and GDP on Poverty in Indonesia - Nasution, Qisti Marhamah; Khoiruddin, Akhmad Yusuf; Slamet Haryono (Jurnal Magister Ekonomi Syariah, 2023)
This research aims to assess the influence of Islamic financial inclusion, urbanization, inflation, and GDP on the alleviation of poverty in Indonesia. The methodology employed is quantitative, utilizing secondary data in a panel data format spanning the period from 2018 to 2022. A total of 165 samples were gathered, and the data underwent processing through Eviews 10. The findings indicate that individually, the Sharia Financial Inclusion Index (IIKS), inflation, and GDP do not exhibit a significant impact on poverty reduction in Indonesia. Conversely, urbanization has a noteworthy and negative effect on poverty reduction in Indonesia. When considered collectively, the IIKS, urbanization, inflation, and GDP variables jointly exert a substantial influence on poverty reduction in Indonesia, reflected in an Adjusted R-squared value of 98%, while the remaining 2% is attributed to other unexplored factors in this study. For future research endeavors, it is advisable to introduce additional variables for a more comprehensive and profound exploration of this subject.